Participation Rates in Epidemiologic Studies - Galea, Sandro; Tracy, Melissa (Annals of epidemiology, 2007)
Participation rates for epidemiologic studies have been declining during the past 30 years with even steeper declines in recent years. This wholesale decrease in participation rate, or at the very least the increase in refusal, has, quite understandably, occasioned some concern among epidemiologists who have long considered a high study participation rate as one of the hallmarks of a “good” epidemiologic study. In this review we synthesize the issues that are central to epidemiologic thinking around declining study participation rates. We consider the reasons why study participation has been declining, summarize what we know about who does participate in epidemiologic studies, and discuss the implications of declining participation rates. We conclude with a discussion of methods that may help improve study participation rates.